2022
DOI: 10.1128/jcm.00431-22
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Nonsputum Diagnostic Testing for Tuberculosis in People with HIV Using Oral Swab PCR and Urine Lipoarabinomannan Detection

Abstract: Testing for mycobacterial lipoarabinomannan (LAM) in urine is a practical but insensitive alternative to sputum testing to diagnose tuberculosis (TB) in people with HIV (PWH). Here, we evaluated urine LAM testing alongside PCR-based tests for Mycobacterium tuberculosis (MTB) DNA in tongue swabs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…QIAmp DNA minikit used to extract DNA. OmniSwabs warmed and extracted using QIAmp DNA minikit In-house PCR (Roche 480 Lightcycler) Molina-Moya 2020, Moldova 31 Adults with a clinical diagnosis of pulmonary tuberculosis 300 Mean 48·8 (SD 14·4) NA 0 Sputum Xpert MTB/RIF or culture 29 PrimeSwab flocked swab 1 buccal swab PrimeStore molecular transport media Vortexed then kept at room temp for up to 30 days or frozen and stored at −20°C DNA extracted with PrimeXtract nucleic acid extraction and purification kit In-house PCR (Roche 480 Lightcycler) Nicol 2019, South Africa 24 Children aged <15 years with presumptive pulmonary tuberculosis 165 2·6 (IQR 1·1–6·8) 113 (68·5%) 18 (11%) Sputum Xpert MTB/RIF or culture or clinical diagnosis 17 GE Healthcare OmniSwab or Puritan Purflock Ultra swab 2 buccal swabs Sterile lysis buffer Frozen and stored at −80°C DNA extracted using QIAmp DNA minikit In-house PCR Shapiro 2022, South Africa 7 Adults aged ≥16 years with HIV and a known pulmonary tuberculosis diagnosis pre-treatment or symptoms of tuberculosis 131 36 (IQR not reported) NA 120 (92%) Sputum Xpert MTB/RIF Ultra or culture 42 Copan FLOQswab 2 tongue swabs 0·5 mL sterile Tris-EDTA buffer Frozen and stored at −80°C until testing Manually processed and concentrated with ethanol In-house PCR (IS 6110 -targeted qPCR [Applied Biosystems StepOnePlus Real-Time PCR system]) Song 2021, China 32 Ad...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QIAmp DNA minikit used to extract DNA. OmniSwabs warmed and extracted using QIAmp DNA minikit In-house PCR (Roche 480 Lightcycler) Molina-Moya 2020, Moldova 31 Adults with a clinical diagnosis of pulmonary tuberculosis 300 Mean 48·8 (SD 14·4) NA 0 Sputum Xpert MTB/RIF or culture 29 PrimeSwab flocked swab 1 buccal swab PrimeStore molecular transport media Vortexed then kept at room temp for up to 30 days or frozen and stored at −20°C DNA extracted with PrimeXtract nucleic acid extraction and purification kit In-house PCR (Roche 480 Lightcycler) Nicol 2019, South Africa 24 Children aged <15 years with presumptive pulmonary tuberculosis 165 2·6 (IQR 1·1–6·8) 113 (68·5%) 18 (11%) Sputum Xpert MTB/RIF or culture or clinical diagnosis 17 GE Healthcare OmniSwab or Puritan Purflock Ultra swab 2 buccal swabs Sterile lysis buffer Frozen and stored at −80°C DNA extracted using QIAmp DNA minikit In-house PCR Shapiro 2022, South Africa 7 Adults aged ≥16 years with HIV and a known pulmonary tuberculosis diagnosis pre-treatment or symptoms of tuberculosis 131 36 (IQR not reported) NA 120 (92%) Sputum Xpert MTB/RIF Ultra or culture 42 Copan FLOQswab 2 tongue swabs 0·5 mL sterile Tris-EDTA buffer Frozen and stored at −80°C until testing Manually processed and concentrated with ethanol In-house PCR (IS 6110 -targeted qPCR [Applied Biosystems StepOnePlus Real-Time PCR system]) Song 2021, China 32 Ad...…”
Section: Resultsmentioning
confidence: 99%
“… 6 Oral swab samples could also be combined with other sample types such as Determine TB LAM Ag (Abbott, Lake Forest, IL, USA) or gastric aspirate in populations with low bacillary burden. 7 One potential clinical pathway for the use of oral swabs is shown in the appendix (p 8) .
Figure 1 Potential sources of variability in sensitivity and specificity for oral swabs LAMP=loop-mediated isothermal amplification.
…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have developed oral swabs, as a non-invasive method for detecting MTB DNA, which can be obtained from the tongue, cheek or gums ( 14 ). While obtaining samples directly from the lower respiratory tract is of paramount importance and demonstrates superior efficacy in diagnosing TB, oral swabs present a more accessible alternative approach for TB diagnosis ( 17 , 25 ). They have also been widely utilized in diagnosing TB in animals ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies reported on testing for rifampicin resistance with Ultra in patients with an HIV-TB co-infection. (18). However, studies at more centers and with larger cohorts need to be conducted to determine Ultra's accuracy when testing various specimens.…”
Section: Correspondencementioning
confidence: 99%